The Affect Of Giving Baby Massage With Lavender Aromatherapy On Improving The Sleep Quality Of Babies Aged 0-12 Months At PMB Puji Handayani Samarinda - Arum, Osiana Paramita; Ariestantia, Dwi Riyan; Lidia, Besse (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Introduction : Babies need quality sleep to support their growth and development. Massaging babies can help stimulate their muscles and nerves so they become comfortable and sleepy. Using lavender aromatherapy can increase the baby's sense of comfort. Purpose : to determine the effect of giving baby massage with lavender aromatherapy on improving the sleep quality of babies aged 0-12 months at PMB Puji Handayani Samarinda. Methods : The research was carried out using an experimental method with a quasi-experimental design research type with one group pretest-post test. The sampling technique is purposive sampling. The respondents in this study were babies aged 0-12 months who met the inclusion criteria as many as 20 respondents. Results : Based on the results of the Wilcoxon test, the data obtained is a calculated Z value, namely a large change value of -3.826, namely an absolute value of Z calculated <0.05 with a p-value of 0.000 <0.05 which is less than the research limit of 0.05 so the hypothesis decision is to accept Ha . Conclusion : There is an influence of baby massage on improving the sleep quality of babies aged 0-12 months. Suggestion : for future researchers who are interested in this research, they can carry out further research on the factors that influence improving the quality of baby sleep.